Fundamentos para la mejora genética de ovinos en Costa Rica (Repertorio Científico, 2021)
Sheep production is an activity of growing importance in Costa Rica, as such, it requires a lot of information transfer and local research development. Local information relevant to developing new breeds with better attributes and genetic gain is scarce. This review addresses the different genetic bases to facilitate the establishment of a sheep genetic improvement program. Various options are described to carry out the selection process and a proposal is made of different crosses in sheep in order to obtain genetically superior animals. The aforementioned crosses are proposed to be carried out with sheep species already established in the country, however, it is applicable in other latitudes according to the improvement objectives.
Keywords: crossover; sheep; selection; genotipe; artificial insemination